Effect of Core Training with and without Yogic Practices on Selected Psychological Variables among College men Athletes - Dr. M. Sundar, Dr. T. Arun Prasanna (International Journal of Advanced Science and Technology, 2019)
The study aims to examine the effect of core strength training with and without yogic practices on sports achievement motivation among college men athletes. To achieve the purpose of the study forty five (N=45) men athletes were selected randomly as subjects from Chennai city, Tamilnadu, India aged between 17 to 25 years. Three groups with fifteen subjects each were selected randomly and named as experimental group - I core strength training group, experimental group - II core strength training with yogic practices and group – III control group. The subjects were tested before and after the twelve weeks of experimentation. The core strength training and the yogic practices were selected as training protocol. The core strength training was given based on stress given in each exercises and sets, and the load was administered between 5 to 10 repetitions in a set with the time labs of 15 to 10 seconds for a set. The training protocol was followed by proper warming up and cooling down regime. The yogic practice was given in the morning time with proper prayer and warming up practice. The load of the yogic practice was increased by the number of yogic practices by 2 to 8 repetitions with 2 to 5 sets. The obtained data from the experimental and control group with the initial and final readings were analysed statistically with analysis of covariance (ANCOVA) and Scheffe’s post hoc test was applied to examine the difference between groups and testing condition. The level of confidence was fixed 0.05. Result of the experimental group had significant improvement on sports achievement motivation when compared to control group. Keywords: Core strength training, Yogic practice, Men Athletes, Sports Achievement Motivation, ANCOVA